2009
DOI: 10.1016/j.ceramint.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of S-doped TiO2 nanoparticles and their photocatalytic ability for degradation of methyl orange

Abstract: A simple synthesis route to nanocrystalline S-doped TiO 2 photocatalysts by a hydrothermal method at 180 8C was developed and the photocatalytic activity of the obtained powders for the degradation of methyl orange was studied. The products were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The phase composition (anatase/rutile ratio) and the photocatalytic activity of the final materials were found to be markedly influenced by the amount of the incorporated sulphur. On i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 21 publications
2
57
0
3
Order By: Relevance
“…When fine crystalline S-doped TiO 2 was synthesized in the study of Ho et al [72] through a simple hydrothermal method, the optical absorption of S-doped TiO 2 in the visible light region increased in tandem with the increase in the S content. This may be related to the finding by Tian et al [71] that the anatase/rutile phase composition ratio was strongly influenced by the amount of S. The phase composition ratio increased with the increase in S amount, with TiO 2 doped with 1.5% S displaying the best crystallite size (around 30 nm).…”
Section: Effect Of Nonmetal Dopingsupporting
confidence: 50%
“…When fine crystalline S-doped TiO 2 was synthesized in the study of Ho et al [72] through a simple hydrothermal method, the optical absorption of S-doped TiO 2 in the visible light region increased in tandem with the increase in the S content. This may be related to the finding by Tian et al [71] that the anatase/rutile phase composition ratio was strongly influenced by the amount of S. The phase composition ratio increased with the increase in S amount, with TiO 2 doped with 1.5% S displaying the best crystallite size (around 30 nm).…”
Section: Effect Of Nonmetal Dopingsupporting
confidence: 50%
“…16 Then, the decoloring rate of the methyl orange, was used to quantify the photocatalytic activities of thin films, and calculated using following equation:…”
Section: 15mentioning
confidence: 99%
“…Doping different elements into TiO 2 , including metal [8,9] and non-metal elements increases the photocatalytic efficiency [10,11]. Researchers indicated that N-containing [12] S-containing [13] or N-doping [14,15] S-doping [16] and N, S co-doping of TiO 2 can improve the visible light response [7].…”
Section: Introductionmentioning
confidence: 99%